XBOX KINECT como rehabilitación motriz en el adulto mayor con accidente cerebrovascular. - Estrada Arévalo, Jonathan Gabriel (2024)
Stroke is an acute onset focal neurological dysfunction caused by a cerebral vascular lesion, making it the leading cause of death worldwide and the third leading cause of disability in survivors. The sequelae in these patients may include hemiplegia, muscle weakness, spasticity, and other relevant clinical manifestations. The Xbox Kinect is an accessory for the Xbox video game console, which uses a combination of cameras and sensors to capture the user's movements, allowing control of the game without the need for a traditional controller. It can also be used in post-stroke rehabilitation. The objective of the research is to analyze the effects generated by the Xbox Kinect device in the treatment of elderly stroke survivors after the collection of articles indexed in scientific databases that support its use in the motor rehabilitation process. The methodology applied was documentary-bibliographic, with inductive method, descriptive design, exploratory level, and qualitative approach. Thirty articles were selected that met the inclusion and exclusion criteria for the research, and then a search was conducted in scientific databases such as PubMed, Science Direct, Scopus, PEDro. The results determined that the Xbox Kinect has more significant benefits when combined with conventional therapy for upper and lower limbs and occupational and mirror therapy. In conclusion, the Xbox Kinect is an innovative complementary method that improves the adherence of older adults to treatment by optimizing neuroplasticity through repetitive activities that improve balance, movement, coordination, and strength.